Clinically Significant Pleural Effusion in Intensive Care: A Prospective Multicenter Cohort Study. (January 2020) - Fysh, Edward T. H.; Smallbone, Portia; Mattock, Nicholas; McCloskey, Cassandra; Litton, Edward; Wibrow, Bradley; Ho, Kwok M.; Lee, Y. C. Gary
Abstract : Objectives: The prevalence and optimal management of clinically significant pleural effusion, confirmed by thoracic ultrasound, in the critically ill is unknown. This study aimed to determine: 1) the prevalence, characteristics, and outcomes of patients treated in intensive care with clinically significant effusion and 2) the comparative efficacy and safety of pleural drainage or expectant medical management. Design: A prospective multicenter cohort study. Setting: ICUs in four teaching hospitals in Western Australia. Patients: Consecutive patients with clinically significant pleural effusions (depth ≥ 2 cm on thoracic ultrasound with clinician-determined adverse effects on patient progress). Interventions: None. Measurements and Main Results: Primary outcome was the change in PaO2 :FIO2 (mm Hg) ratio from baseline to 24 hours. Changes in diagnosis and treatment based on pleural fluid analysis and pleural effusion related serious adverse events between those who underwent either drainage within 24 hours or expectant management were compared. Of the 7, 342 patients screened, 226 patients (3.1%) with 300 pleural effusions were enrolled. Early drainage of pleural effusion occurred in 76 patients (34%) and significantly improved oxygenation (PaO2 :FIO2 ratio 203 at baseline vs 263 at 24 hr, +29.6% increment; p < 0.01). This was not observed in the other 150 patients who had expectant management (PaO2 :FIO2 ratio 250 at baseline vs 268 at 24 hr, +7.2% increment; p = 0.44). The improvement in oxygenation after early drainage remained unchanged after adjustment for a propensity score on the decision to initiate early drainage. Pleural effusion related serious adverse events were not different between the two groups (early drainage 10.5% vs no early drainage 16.0%; p = 0.32). Improvements in diagnosis were noted in 91 initial (nonrepetitive) drainages (76.5% out of 119); treatment strategy was optimized after 80 drainage episodes (59.7% out of 134). Conclusions: Early drainage of clinically significant pleural effusion was associated with improved oxygenation and diagnostic accuracy without increased complications. Abstract : Supplemental Digital Content is available in the text.